Student understanding, attitude and achievement: assessment comparisons in genetics and photosynthesis/respiration - McCalla, Serena (Curtin University, 2014)
In the Living Environment Regents examination in New York State, there is a distinct difference between students’ ability to memorize compared to their understanding biological concepts. Consequently, this study compared a range of diagnostic assessment tools to ascertain students’ conceptual understanding in two-selected domains - photosynthesis/respiration and genetics. The Regents examination was not an adequate measure of advanced student understanding of these domains when triangulated against scores on diagnostic examinations, student opinion, and attitudes.